THE EFFECT OF THREE DIMENSIONAL MEDIA TO INCREASE STUDENT LEARNING RESULT IN CUBE AND BEAM MATERIALS IN CLASS V SD STATE 21 MENDO WEST - Nurwindi Nurwindi; Aprian Giosaputra (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract:The problem in this research study is the low of the result of class V student at SD Negeri 21 Mendo West and the absence of media used in the lesson of Mathematics. The purpose of this study is to Determine the influence of Three Dimensional Media to improve student learning outcomes on the material of cubes and blocks in Class V Elementary School 21 West Mendo. This research uses quantitative research with "pre-experimental" method (The one group pretest-posttest design). The sampling technique used in this study saturated sampling. The sample of this study is the entire class V amounted to 34 students. Data collection techniques used in the form of a written test that consists of five essays namely pretest and posttest. The prerequisite test used is the Liliefors test to test the normality of the data. Based on test results Obtained Liliefors that the the data is normally distributed. Based on hypothesis testing analysis of data from the result of t-test pairwise the data related with tcount> TTable (11.95> 2:03), hence can be interpreted that Ha accepted and H0 is rejected. So from the results of the research shows there are positive effects of three-dimensional media to improve student learning outcomes on materials cube and beam Class V Elementary School 21 West Mendo. Keywords: Learning Outcomes, Three Dimensional Media Abstrak: Permasalahan dalam penelitian ini adalah rendahnya hasil belajar siswa kelas V di SD Negeri 21 Mendo Barat dan tidak adanya media yang digunakan dalam pelajaran Matematika. Tujuan penelitian ini adalah untuk mengetahui pengaruh Media Tiga Dimensi untuk meningkatkan hasil belajar siswa pada materi kubus dan balok di Kelas V SD Negeri 21 Mendo Barat. Penelitian ini menggunakan penelitian kuantitatif dengan metode “pre Experimental” (The One Group Pretest-Posttest Design). Teknik pengambilan sampel pada penelitian ini menggunakan sampling jenuh. Sampel penelitian ini seluruh kelas V berjumlah 34 siswa. Teknik pengumpulan data yang digunakan berupa tes tertulis yang terdiri 5 essay yaitu pretest dan posttest. Uji prasyarat yang digunakan adalah uji Liliefors untuk menguji normalitas data. Berdasarkan hasil uji Liliefors diperoleh bahwa data berdistribusi normal. Berdasarkan analisis data uji hipotesis dari hasil perhitungan uji t-test related data berpasangan dengan thitung > ttabel (11,95 > 2,03), maka dapat diartikan bahwa Ha diterima dan H0 ditolak. Jadi dari hasil penelitian menunjukkan terdapat pengaruh positif media tiga dimensi untuk meningkatkan hasil belajar siswa pada materi kubus dan balok kelas V SD Negeri 21 Mendo Barat. Kata Kunci: Hasil Belajar, Media Tiga Dimensi